Thermo-electrical behaviour of cyclic olefin copolymer/exfoliated graphite nanoplatelets nanocomposites foamed through supercritical carbon dioxide. (May 2019) - Dorigato, A; Biani, A; Bonani, W; Pegoretti, A
In this work, novel electrically conductive cyclic olefin copolymer/exfoliated graphite nanoplatelets foams were prepared through a supercritical carbon dioxide treatment starting from the corresponding unfoamed materials prepared by melt compounding, in order to investigate their thermo-electrical properties. For both unfoamed and foamed samples, the exfoliated graphite nanoplatelets introduction led to a systematic enhancement of the thermal degradation temperature. Dynamic-mechanical thermal analysis revealed that the nanofiller addition promoted an enhancement of the storage modulus and of the glass transition temperature over the whole range of the applied foaming pressures. While for unfoamed materials exfoliated graphite nanoplatelets introduction determined an important decrease of the electrical resistivity, the foaming process induced the breakage of the conductive path, with a consequent increase of electrical resistivity. Evaluation of the surface heating upon voltage application showed that the surface temperature of unfoamed materials could be noticeably increased at relatively low voltage levels, while a less pronounced surface heating could be obtained with the corresponding nanocomposite foams.